RANDOMNESS TESTING OF SEQUENCES PRODUCED BY P-ARY GENERALIZED SELF-SHRINKING GENERATOR USING APPROXIMATE ENTROPY: RANDOMNESS TESTING OF SEQUENCES PRODUCED BY P-ARY GENERALIZED SELF-SHRINKING GENERATOR USING APPROXIMATE ENTROPY - Tasheva, Zhaneta; Tasheva, Antoniya (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In this paper a supervene testing for sequences generated by p-ary Generalized Self-Shrinking Generator (pGSSG) is made. Thanks to the Approximate Entropy (ApEn) approach certain randomness properties are proved to be possessed by them. In order to test the applicability of the generator the pGSSG sequence minimum length in excess of which it can be considered that the sequence behaves as truly random is detected.